Allergen immunotherapy in allergic rhinitis: current use and future trends - Klimek, Ludger; Pfaar, Oliver (Expert review of clinical immunology, 2017)
Introduction: Type-1 allergies are among the most chronic common diseases of humans. Allergen immunotherapy (AIT) is the only causative and disease-modifying treatment option besides allergen avoidance. Severe systemic adverse allergic reactions may be induced by every AIT treatment. Different approaches have been used to provide safer AIT preparations to lower or even totally overcome this risk.Areas covered: A structured literature recherche in Medline and Pubmed under inclusion of national and international guidelines and Cochrane meta-analyses has been performed aiming at reviewing clinical use of such approaches in AIT.New allergen preparations may include allergoids, recombinant allergens (recA) and modified recombinant allergens (recA) in subcutaneous as well as in mucosal immunotherapies (application e.g. using bronchial, nasal, oral and sublingual application) with sublingual being the established mucosal application route and new ways of application like intralymphatic and epicutaneous immunotherapy.Expert commentary: Immune-modifying agents like Virus-like particles and CpG-motifs, adjuvants like MPL and aluminum hydroxide are evaluated and found to increase and direct the immunological response toward immunological tolerance.New forms of allergen extracts can improve safety and efficacy of AIT and may change our way of performing allergen immunotherapy in the future.